If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(c + -4) = 8(c + -6) Reorder the terms: 7(-4 + c) = 8(c + -6) (-4 * 7 + c * 7) = 8(c + -6) (-28 + 7c) = 8(c + -6) Reorder the terms: -28 + 7c = 8(-6 + c) -28 + 7c = (-6 * 8 + c * 8) -28 + 7c = (-48 + 8c) Solving -28 + 7c = -48 + 8c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-8c' to each side of the equation. -28 + 7c + -8c = -48 + 8c + -8c Combine like terms: 7c + -8c = -1c -28 + -1c = -48 + 8c + -8c Combine like terms: 8c + -8c = 0 -28 + -1c = -48 + 0 -28 + -1c = -48 Add '28' to each side of the equation. -28 + 28 + -1c = -48 + 28 Combine like terms: -28 + 28 = 0 0 + -1c = -48 + 28 -1c = -48 + 28 Combine like terms: -48 + 28 = -20 -1c = -20 Divide each side by '-1'. c = 20 Simplifying c = 20
| 7x+11x=108 | | 3x+12=17.2 | | 2x^3-5x^2-28x+15=0 | | 5x-16=-4x+2 | | (3x-3)(2x-2)= | | 3+3(3n+6)-n= | | -6m-6(m+6)=-132 | | 2ux-5u+ux-3u= | | (x+8)(x-6)= | | 0=-2(y+6) | | 6(-1-7n)-2n=-314 | | -2(-4v+y)-6(-3y-2v)= | | x+18+4x=-46-4x-53 | | k=1.6*665 | | 1=-8 | | (3x-3)(4x+2)= | | 3n-6(3n-6)=111 | | y+15-2=0 | | k=1.6*655 | | u+21=8 | | (5x+6)(2x+1)= | | 1.1(2.5x-3.5)=11.2 | | -12(0)+16=16+10(0) | | 2v-8(8-2v)=-82 | | (4x+4)(2x+1)= | | X+14=152 | | -12+16=16+10 | | (-x+1)(3x-8)= | | -8-9x=163 | | k=1.6*430 | | I=1.6*430 | | y=-18x^2+321 |